Enhanced Activation Energy of Crystallization of Pure Zirconia Nanopowders Prepared via an Efficient Way of Synthesis Using NaBH4. Issue 11 (18th October 2013) - Nayak, Nadiya B.; Nayak, Bibhuti B.; Mondal, Aparna
Abstract : An efficient way through borohydride synthesis route using NaBH4 was performed to prepare pure zirconia nanopowders via three different conditions such as gelation, precipitation, and constant pH. Zirconia powders prepared through constant pH route show highest activation energy of crystallization ( E a  = 260 kJ/mol) or higher exothermic peak temperature (717°C), when compared with gelation or precipitation route due to its controlled growth of smaller crystallites. The released huge amount of H2 gas bubbles during borohydride synthesis via constant pH route play a major role for formation of loose smaller crystallites and thus enhances the activation energy of crystallization of pure zirconia. So, the as‐prepared zirconia powders prepared through constant pH route remain amorphous up to 600°C and pure t‐ZrO2 (~20 nm) was stable up to 800°C.